The Effect of Video Blog (Vlog) to Students' Speaking Skill on Junior High School - Mahrus; Mariyatul Kiptiyah (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2024)
In this study, researchers found English language learning problems that emerged from students, teacher strategies and learning facilities. This fear can hinder students' progress and self-confidence, some students do not yet have good English speaking skills, students still have difficulty telling their daily activities in front of the camera, so students take action. Researchers utilize technology that is often encountered by students in everyday life apart from learning English. The media is a video blog (Vlog). from this Video Blog can be the right solution because students can improve their English speaking skills as well as take advantage of technology.